Knockdown Screens to Knockout HIV-1 - Goff, Stephen P. (2008)
Three recent screens use siRNAs to identify host genes that are critical for HIV-1 replication. These screens have uncovered hundreds of human genes not previously known to be commandeered by the virus during infection. Although some caveats remain, this screening approach opens up a new landscape of viral-host interactions for future exploration.